The usefulness of SAGE score in predicting high pulse wave velocity in hypertensive patients: a retrospective cohort study - Pereira, Luiz Carlos Carneiro; Chagas, Patrícia; Barbosa, Eduardo Costa Duarte; Barroso, Weimar Kunz Sebba; Oliveira, Adriana Camargo; Hillesheim, Suélen Feijó; Kohlrausch, Vitória Carolina; Chemello, Diego (Frontiers in Cardiovascular Medicine, 2024)
Introduction Aortic stiffness assessed by pulse wave velocity (PWV) is an important predictor to evaluate the risk of hypertensive patients. However, it is underutilized in clinical practice. We aimed to identify the optimal cutoff SAGE score that would indicate a risk PWV ≥ 10 m/s in Brazilian ambulatory hypertensive patients. Materials and methods A retrospective cohort study. Patients underwent central blood pressure measurement using a validated oscillometric device from August 2020 to December 2021. A ROC curve was constructed using the Youden statistic to define the best score to identify those at high risk for PWV ≥ 10 m/s. Results A total of 212 hypertensive individuals were selected. The mean age was 64.0 ± 12.4 years and 57.5% were female. The following comorbidities were present: overweight (47.6%), obesity (34.3%), and diabetes (25.0%). Most of the sample (68.9%) had PWV < 10 m/s. According to Youden's statistic, a cutoff point of 6 provided the optimal combination of sensitivity and specificity for identifying patients with a PWV ≥ 10 m/s. This cutoff achieved sensitivity of 97.0%, and specificity of 82.9%. In clinical practice, however, a cutoff point of 7 (where score values of at least 7 were considered to indicate high risk) had a positive likelihood ratio of 8.2 and a negative likelihood ration of 0.346, making this the ideal choice by accurately excluding patients who are less likely to have PWV ≥ 10 m/s. Conclusion A SAGE score ≥7 identified Brazilian hypertensive patients with a high risk of PWV ≥ 10 m/s.